Tingkat Kecemasan Ibu Postpartum Berhubungan dengan Keterlambatan Pengeluaran ASI pada Masa Pandemi Covid-19 - malik, Melyana; Gasma, Asmawati; Ningsi, Agustina (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2022)
Anxiety is a subjective emotion that makes an individual uncomfortable, an unclear fear and anxiety, which is accompanied by autonomic responses. In the Covid-19 pandemic condition, the prevalence of postpartum maternal anxiety levels is increasing, this is related to the process of breastfeeding formation and excretion, namely the milk production reflex and let down reflex, both of which are closely related to hormones regulated by the hypothalamus. So that the higher the level of anxiety in the mother, the more inhibiting the production of breast milk in postpartum mothers.This study aims to analyze the relationship between postpartum anxiety level and breast milk production during the Covid-19 epidemic at the Antang Perumnas Health Center, Makassar City. This type of research is an analytic survey, with a cross sectional observation design. The sampling technique uses